Flow line master batch as well as preparation method and application thereof

By adding specific components to the PP matrix material, the compatibility between PPE and PP is improved, and the problem of poor compatibility between the existing flow masterbatch and PP matrix resin is solved, and the good flow effect and color difference effect of the plate is achieved.

CN119798848AActive Publication Date: 2025-04-11KINGFA SCI & TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411988091.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing flow masterbatch has poor compatibility with PP matrix resin, which leads to easy peeling, uneven textures and high cost during the continuous extrusion of the sheet.

Method used

By adding components such as PPE, PS, polypropylene grafted styrene and polypropylene grafted glycidyl methacrylate to the PP matrix material, the compatibility of PPE and PP is improved, and the melting point and heat resistance of the flow masterbatch are improved.

Benefits of technology

The good compatibility between the flow masterbatch and the PP matrix resin is achieved, melting is avoided, and the sheet material is formed evenly lines and has good flow effect, and the color difference between the sheet material matrix is ​​large, which is suitable for decorative boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a flow line master batch as well as a preparation method and application thereof, and belongs to the field of high polymer materials. According to the flow line master batch, PP is used as matrix resin, PPE is added to improve the melting point, PS, polypropylene grafted styrene and polypropylene grafted glycidyl methacrylate are added to improve the compatibility of PPE and PP, and the flow line master batch has a high melting point, is good in compatibility with the board matrix resin PP in the continuous extrusion process of a board, is not prone to melting and is good in flow line effect; the color difference with a plate substrate is high; and the plate substrate is not dyed, has low color difference with the standard color, and is suitable for preparing the decorative plate with the flow line pattern.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and in particular to a rhytide masterbatch and a preparation method and application thereof. Background Art

[0002] Continuously extruded boards are widely used in building walls, home decoration roofs and floors, public facilities floors, etc. They mainly play the role of moisture-proofing, weather-resistant and heat-insulating, and beautifying walls and floors. For floor boards for home decoration and public facilities, the industry usually uses rhytmographic masterbatch to achieve the imitation wood grain effect on the board surface during the continuous extrusion process of the board. This requires that the rhytmographic masterbatch is compatible with the board matrix resin, but cannot be completely melted during the extrusion process to avoid complete fusion with the board matrix resin and the inability to achieve the grain effect. Since boards often use PP or PE as the matrix material, the demand for a high-melting-point PP matrix material rhytmographic masterbatch has become increasingly prominent. However, the current rhytmographic masterbatch base materials on the market are mainly high-melting-point engineering resins, such as PA, PBT, etc., which have poor compatibility with the board matrix PP, and are prone to peeling, uneven grain, high cost and other problems. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of this application is to provide a flow pattern masterbatch and its preparation method and application. The obtained flow pattern masterbatch has a high melting point. During the continuous extrusion process of the sheet, it not only has good compatibility with the sheet matrix resin PP, but is also not easy to melt and has a good flow pattern effect.

[0004] In order to achieve the above objectives, in a first aspect, the present application provides a rhytometric masterbatch comprising the following components in parts by weight:

[0005]

[0006] PPE has a high melting point and good heat resistance. Adding a specific amount of PPE to PP can improve its melting point and heat resistance, but the compatibility between PPE and PP is poor. By adding a specific amount of PS, polypropylene grafted styrene and polypropylene grafted glycidyl methacrylate to improve the compatibility between PPE and PP, PS and PP are partially compatible, and the use of polypropylene grafted styrene can improve the compatibility between the two, promote better dispersion of PS in PP, and form a PS island phase; PS and PPE are completely compatible, and good dispersion of PS in PP is conducive to improving the dispersibility of PPE in PP; polypropylene grafted glycidyl methacrylate can further improve the compatibility of PPE and PP.

[0007] The flow pattern masterbatch has a higher melting point under the joint action of the above-mentioned specific contents of each component. During the continuous extrusion process of the sheet, it not only has good compatibility with the sheet matrix resin PP, but is also not easy to melt. It has good flow pattern effect, uniform lines, and a high color difference with the sheet matrix; the sheet matrix is ​​not dyed and has a low color difference with the standard color.

[0008] Preferably, the melt flow rate of the PS at 200° C. and 5 kg is 0.5 to 7 g / 10 min. More preferably, the melt flow rate of the PS at 200° C. and 5 kg is 0.8 to 4.2 g / 10 min.

[0009] Controlling the melt flow rate of PS at 200°C and 5kg within the range of 0.5-7g / 10min, especially within the range of 0.8-4.2g / 10min, is beneficial to increasing the size of the dispersed phase formed by PS, so that PPE can be better and more easily dispersed in PS, thereby making the dispersion of PPE in PS better and the flow effect better.

[0010] The melt flow rate of the PS can be measured according to ISO 1133-2022.

[0011] Preferably, the intrinsic viscosity of the PPE is 33 to 55 mL / g. More preferably, the relative viscosity of the PPE is 35 to 38 mL / g.

[0012] Controlling the intrinsic viscosity of PPE within the range of 33-55 mL / g, especially within the range of 35-38 mL / g, is conducive to smoother diffusion of PPE in the PP continuous phase and faster and more uniform entry into the PS dispersed phase, thereby making the dispersion of PPE in PS better and the flow effect better.

[0013] The intrinsic viscosity of the PPE can be measured according to GB / T 41874-2022 Plastic polyphenylene ether (PPE) resin, using the Ubbelohde viscometer method.

[0014] Preferably, the melt flow rate of the PP at 230° C. and 2.16 kg is 0.1 to 5 g / 10 min. More preferably, the melt flow rate of the PP at 230° C. and 2.16 kg is 0.2 to 1.5 g / 10 min.

[0015] Controlling the melt flow rate of the PP at 230° C. and 2.16 kg to 0.1 to 3.5 g / 10 min, especially 0.2 to 1.5 g / 10 min, is beneficial to the diffusion of PS and PPE, so that the PPE has better dispersion in PS and better flow effect.

[0016] The melt flow rate of the PP can be measured according to ISO 1133-2022.

[0017] Preferably, the grafting rate of styrene in the polypropylene grafted styrene is 0.5 wt.% to 12 wt.%. More preferably, the grafting rate of styrene in the polypropylene grafted styrene is 10 wt.% to 12 wt.%, so as to achieve better flow effect.

[0018] Preferably, the grafting rate of glycidyl methacrylate in the polypropylene grafted with glycidyl methacrylate is 0.5wt.% to 3wt.%. More preferably, the grafting rate of glycidyl methacrylate in the polypropylene grafted with glycidyl methacrylate is 2wt.% to 3wt.%, so as to achieve better flow effect.

[0019] Preferably, the colorant includes at least one of carbon black, black iron oxide, a mixture of chrome yellow and titanium dioxide, and a mixture of iron oxide red and titanium dioxide, wherein the mass ratio of chrome yellow to titanium dioxide in the mixture of chrome yellow and titanium dioxide is (0.5-2):1, and the mass ratio of iron oxide red to titanium dioxide in the mixture of iron oxide red and titanium dioxide is (0.5-2):1.

[0020] Preferably, the rhytide masterbatch further comprises the following components in parts by weight:

[0021] Light stabilizer 0.1-1 part;

[0022] Antioxidant 0.2 to 1 part.

[0023] Adding light stabilizers and antioxidants to rhyometry masterbatch is beneficial to improving the weather resistance of the material and extending its service life.

[0024] Preferably, the antioxidant comprises a first antioxidant and a second antioxidant, the weight ratio of the first antioxidant to the second antioxidant is (1-5): (1-3), the first antioxidant is a triazine antioxidant, and the second antioxidant is a thioester antioxidant. Combining the triazine antioxidant and the thioester antioxidant and controlling the mass ratio of the two within the range of (1-5): (1-3) can synergistically improve the antioxidant properties of the material, thereby synergistically improving the weather resistance of the material. The weight ratio of the first antioxidant to the second antioxidant can be selected as 1:3, 1:2:, 1:1, 3:1, 4:1 or 5:1, etc. As an example, the triazine antioxidant can select at least one of antioxidant 1010 and antioxidant 1790; the thioester antioxidant can select at least one of antioxidant 412SDSTDP.

[0025] Preferably, the light stabilizer comprises a hindered amine light stabilizer.

[0026] Preferably, the weight percentage of PP in the rhytographic masterbatch is above 25%, such as 25%, 30%, 40%, 50%, 60%, 70% or 75%.

[0027] In a second aspect, the present application provides a method for preparing a flow pattern masterbatch, comprising the following steps: mixing and dispersing all raw materials, melt-extruding, and granulating to obtain the flow pattern masterbatch.

[0028] Preferably, the temperature of the melt extrusion is 230-260°C.

[0029] In a third aspect, the present application provides the use of the rhytide masterbatch in preparing a board with a rhytide pattern. The rhytide masterbatch can be used to prepare floor boards with rhytide patterns in places such as home decoration and public facilities.

[0030] In a fourth aspect, the present application further provides a plate having a flow pattern, comprising the following components in parts by weight:

[0031] PP 100 copies;

[0032] The rhyolite masterbatch is 0.3 to 3 parts.

[0033] Preferably, the weight percentage of PP in the sheet material having the flow pattern is above 97%, such as 97%, 98%, 99% or 99.7%.

[0034] In a fifth aspect, the present application also provides the use of the plate with the flow pattern in the decoration of building floors or exterior walls.

[0035] Compared with the prior art, the beneficial effects of this application are:

[0036] (1) The flow masterbatch of the present application uses PP as the base resin, adds a specific amount of PPE to improve its melting point, and improves the compatibility of PPE and PP by adding a specific amount of PS, polypropylene grafted styrene and polypropylene grafted glycidyl methacrylate.

[0037] (2) The flow pattern masterbatch of the present application has a relatively high melting point under the combined effect of the above-mentioned specific contents of the various components. During the continuous extrusion process of the sheet, it not only has good compatibility with the sheet matrix resin PP, but is also not easy to melt. It has a good flow pattern effect, uniform lines, and a high color difference with the sheet matrix. The sheet matrix is ​​not dyed and has a low color difference with the standard color, and is suitable for preparing decorative sheets with flow pattern patterns. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0039] The raw materials used in the following examples and comparative examples are shown in Table 1, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind.

[0040] PP 1: melt flow rate at 230°C and 2.16 kg is 0.5 g / 10 min, brand: 6600A, supplier: Taiwan Plastics;

[0041] PP 2: melt flow rate at 230°C and 2.16 kg is 0.3 g / 10 min, brand: PP B8101, supplier: Yanshan Petrochemical;

[0042] PP 3: melt flow rate at 230°C and 2.16 kg is 1 g / 10 min, brand: EPS30R, supplier: Dushanzi Petrochemical;

[0043] PP 4: melt flow rate at 230°C and 2.16 kg is 3 g / 10 min, brand: PP L5E89, supplier: Sichuan Petrochemical;

[0044] PS1: melt flow rate at 200°C and 5kg is 3.1 g / 10min, brand: 8265, supplier: INEOSSTYROLUTION;

[0045] PS2: melt flow rate at 200°C and 5kg is 1g / 10min, brand: EA3300, supplier: Astor;

[0046] PS 3: melt flow rate at 200°C and 5kg is 4g / 10min, brand: PS 350K, supplier: Guoqiao;

[0047] PS 4: melt flow rate at 200°C and 5kg is 5g / 10min, brand: HP8250, supplier: Taiwan Chemical;

[0048] PPE 1: intrinsic viscosity IV1 meets: 37mL / g, brand: LXN035, supplier: Nantong Xingchen;

[0049] PPE 2: intrinsic viscosity IV2 meets: 50mL / g, brand: LXN050, supplier: Nantong Xingchen;

[0050] Polypropylene grafted styrene 1: styrene grafting rate 10wt.%, brand: 1616FA, supplier: BYK Chemical;

[0051] Polypropylene grafted styrene 2: Styrene and initiator DBTH are dispersed in methanol until there is no precipitation, poured into PP powder, stirred until the powder has no wet feeling, spread on a surface dish, and left to air-dry for 24 hours to obtain an intermediate product. 0.5 g of the intermediate product is added to 1000 mL of toluene (toluene is excessive), condensed, refluxed, stirred and heated until the intermediate product is completely dissolved, and then 1500 mL of methanol (methanol is excessive) is added for flocculation and precipitation, filtered, and the obtained precipitate is dried to obtain polypropylene grafted styrene 2 with a grafting rate of 8 wt.%, wherein the weight of styrene is 12% and the weight of initiator DBTH is 4% based on the weight of PP, and the amount of methanol used is the minimum amount required to completely dissolve styrene. Styrene is purchased from Denka of Japan, and polypropylene uses PP 320 from Maoming Shihua.

[0052] Polypropylene grafted with glycidyl methacrylate 1: glycidyl methacrylate grafting rate 2.5wt.%, brand: 8104FA, supplier: BYK Chemical;

[0053] Polypropylene grafted with glycidyl methacrylate 2: prepared with reference to CN116003914B, with a glycidyl methacrylate grafting rate of 0.5 wt.%, wherein the polypropylene is PP 320 from Maoming Shihua, and the glycidyl methacrylate is from SigmaAldrich;

[0054] Polypropylene grafted with maleic anhydride: grafting rate 1wt.%, brand: 1001CN, supplier: Bondyram;

[0055] Carbon black: Carbon black masterbatch 2772, supplier: Cabot, containing 40wt.% pure carbon black. The amount of carbon black in Table 1 and Table 2 has been converted into the amount of pure carbon black;

[0056] Light stabilizer: UV-3808PP5, commercially available;

[0057] The first antioxidant: antioxidant 1790, commercially available;

[0058] Second antioxidant: antioxidant 412S, commercially available.

[0059] The following embodiments and comparative examples all provide a flow masterbatch, comprising the following steps: all raw materials are mixed and dispersed, and then fed into a twin-screw extruder for granulation to obtain the flow masterbatch, wherein the melt mixing temperature is 230-260°C.

[0060] The formulas of the flow masterbatches of these embodiments and comparative examples are shown in Tables 1 and 2, and the flow masterbatches are subjected to the following performance tests, and the test results are shown in Tables 1 and 2:

[0061] 1. Determine the melting point of the rhytometric masterbatch according to the ASTM D3418-2015 method. If the melting point is higher than 175℃, it is qualified; otherwise, it is unqualified.

[0062] 2. Mix the flow masterbatch with PP (melt flow rate of 0.5g / 10min at 230℃ and 2.16kg, brand: PPB8101, supplier: Yanshan Petrochemical) at a mass ratio of 2%:1, disperse, extrude at 200℃, screw speed 50rpm, vacuum degree -0.1MPa to obtain a plate with a length of 1.2m, a width of 15cm, and a thickness of 5cm. The following performance tests are performed on the plate:

[0063] Referring to ASTM E1347-06 (2020), a colorimeter is used to measure the color difference △E1 between the flow pattern and the plate substrate, as well as the color difference △E2 between the plate substrate and the standard color (i.e., the plate extruded using only Yanshan Petrochemical's PP B8101 using the same process as mentioned above). The average value is calculated by randomly measuring 5 values. If the average value of △E1 is greater than 3 and the average value of △E2 is less than 2, the flow pattern effect is good, otherwise the flow pattern effect is not good.

[0064] Table 1

[0065]

[0066] Table 2

[0067]

[0068]

[0069] It can be seen from the above data that the flow pattern masterbatch in each embodiment has a high melting point and has a good flow pattern effect in the plate matrix PP. For example, the melting point of the flow pattern masterbatch is above 172°C, the average color difference △E1 between the flow pattern and the plate matrix is ​​greater than 3, and the average color difference △E2 between the plate matrix and the standard color is less than 2.

[0070] Comparative Examples 1 and 2 did not add PPE, and the melting point of the grain masterbatch was low. During the continuous extrusion of the sheet, the grain masterbatch was completely melted, resulting in the inability to form grains.

[0071] Comparative Examples 3 to 7 do not add PS, or do not add polypropylene grafted styrene, or use other compatibilizers instead of polypropylene grafted styrene, or do not add polypropylene grafted glycidyl methacrylate, or use other compatibilizers instead of polypropylene grafted glycidyl methacrylate, resulting in poor compatibility between PPE and PP, and a deviation in the flow effect.

[0072] From the comparison of Examples 5, 6 to 8, it can be seen that the melt flow rate of PP will affect the flow effect. To obtain a better flow effect, the melt flow rate of PP at 230°C and 2.16 kg is preferably 0.2 to 1.5 g / 10 min.

[0073] From the comparison of Examples 5 and 9 to 11, it can be seen that the melt flow rate of PS will affect the flow effect. To obtain a better flow effect, the melt flow rate of PS at 200° C. and 5 kg is preferably 0.8 to 4.2 g / 10 min.

[0074] Comparison of Examples 5 and 12 shows that the relative viscosity of PPE will affect the flow effect. To obtain a better flow effect, the relative viscosity of PPE is preferably 35 to 38 mL / g.

[0075] The flow masterbatch obtained in Example 5 was mixed with PP (melt flow rate of 0.5 g / 10 min at 230° C. and 2.16 kg, brand: PP B8101, supplier: Yanshan Petrochemical) at a mass ratio of 0.5%:1, dispersed, and extruded and injection molded at 200° C. to obtain plate A.

[0076] The flow masterbatch obtained in Example 5 was mixed with PP (melt flow rate of 0.5 g / 10 min at 230° C. and 2.16 kg, brand: PP B8101, supplier: Yanshan Petrochemical) at a mass ratio of 2.5%:1, dispersed, and extruded and injection molded at 200° C. to obtain plate B.

[0077] The △E1 and △E2 of plates A and B were measured according to the above method. The measurement results are shown in Table 3.

[0078] Table 3

[0079] Plate A Plate B <![CDATA[Color difference △E1 with the sheet body]]> 5.9 12.2 <![CDATA[Color difference △E2 between the extrusion board color and the standard color]]> 0.4 0.9

[0080] It can be seen that both plates A and B have good flow effect.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A rhyolite masterbatch, characterized in that: It comprises the following components in parts by weight:

2. The rhytide masterbatch according to claim 1, characterized in that The melt flow rate of the PS at 200° C. and 5 kg is 0.5 to 7 g / 10 min, preferably 0.8 to 4.2 g / 10 min.

3. The rhytide masterbatch according to claim 1, characterized in that The intrinsic viscosity of the PPE is 33 to 55 mL / g, preferably 35 to 38 mL / g.

4. The rhytide masterbatch according to claim 1, characterized in that The melt flow rate of the PP at 230° C. and 2.16 kg is 0.1 to 3.5 g / 10 min or less, preferably 0.2 to 1.5 g / 10 min.

5. The rhytide masterbatch according to claim 1, characterized in that: Also includes the following components in parts by weight: Light stabilizer 0.1-1 part; Antioxidant 0.2 to 1 part.

6. The rhytide masterbatch according to claim 5, characterized in that: At least one of the following conditions is met: S1. The colorant includes at least one of carbon black, black iron oxide, a mixture of chrome yellow and titanium dioxide, and a mixture of iron oxide red and titanium dioxide, wherein the mass ratio of chrome yellow to titanium dioxide in the mixture of chrome yellow and titanium dioxide is (0.5-2):1, and the mass ratio of iron oxide red to titanium dioxide in the mixture of iron oxide red and titanium dioxide is (0.5-2):1; S2, the light stabilizer includes a hindered amine light stabilizer; S3. The antioxidant includes a first antioxidant and a second antioxidant, the weight ratio of the first antioxidant to the second antioxidant is (1-5):(1-3), the first antioxidant is a triazine antioxidant, and the second antioxidant is a thioester antioxidant.

7. The method for preparing a rhytide masterbatch according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing and dispersing all raw materials, melting and extruding, and granulating to obtain flow pattern master batch.

8. Use of the rhytide masterbatch as claimed in claim 1 in preparing a plate having a rhytide pattern.

9. A plate having a flow pattern, characterized in that: The composition comprises the following components in parts by weight: PP 100 copies; 0.3 to 3 parts of the rhytide masterbatch according to any one of claims 1 to 6.

10. Use of the plate with flow pattern as claimed in claim 9 in decoration of building floors or exterior walls.

Citation Information

Patent Citations

  • Automotive resin composition and its preparation method

    CN102516743A

  • Multi-monomer melt-grafted polypropylene-grafted masterbatch compatibilizer

    CN102603979A

  • Spraying-free aesthetic resin composition with bowlder effect and preparation method thereof

    CN104479283A

  • Imitated wood grain color master batch, polyethylene composite material and preparation method of polyethylene composite material

    CN107629317A

  • Functional master batch as well as preparation method and application thereof

    CN114605768A